The spillover of shadow interest rate to the excess returns in emerging markets - Oguzhan Ozcelebi; Mehmet Tevfik Izgi (Universitas Islam Indonesia, 2021)
Purpose - This study focuses on the monetary policy transmission of the U.S. on the excess returns in emerging markets by estimating the impacts of changes in the shadow interest rate in the U.S. on the Barclays Benchmark EM FX Trend Excess Return Index (FXERI) and the Barclays Cross Asset Trend Index – EM FX ER (CRASERI).Methods - To account for the spillover effects of the macroeconomic and financial variables, this study employs a bivariate VARMA–AGARCH approach. This study employs 206 daily observations, from February 22, 2002, to July 5, 2019 sourced from The Barclays database and the Reserve Bank of New ZealandFindings - This study finds that the shocks in shadow interest rates will decrease the Barclays Benchmark EM FX Trend Excess Return Index (FXERI) and the Barclays Cross Asset Trend Index – EM FX ER (CRASERI) in the short term. The results of VARMA–BEKK–AGARCH model show that changes/shocks in shadow interest rates will reduce the excess returns in the financial markets of emerging countries in the long term.Implication - The study reveals that a high-interest rate policy could be used as a tool by the FED to prevent excessive returns on emerging countries' financial marketsOriginality - This study contributes to the existing literature by addressing the issue of whether the monetary policy stance of the U.S. after the Global Financial Crisis (GFC) can be recognized as the primary source of the currency excess returns and multiple-asset class excess returns for emerging countries.